Marine Fungi – An Expandable Source for Production of Novel Bioactive Metabolites: A Comprehensive Review - Prikshit Rampal 1 *; Mukesh Chander1 (International Journal of Fungi, 2026)
The marine environment, representing the largest and most extreme biome on Earth, serves as an unparalleled reservoir of biodiversity. Within this vast ecosystem, marine fungi have emerged as a prolific source of structurally diverse and pharmacologically active secondary metabolites. Dwelling in habitats characterized by extreme high salinity, high hydrostatic pressure, and low temperatures, these microorganisms have evolved unique biochemical and metabolic pathways to synthesize novel compounds, including pyrrole-imidazole alkaloids, cyclic dipeptides, polyketides, and terpenoids. This comprehensive review evaluates the recent advancements in the discovery, isolation, and functional characterization of bioactive metabolites from marine-derived and endophytic fungi. It extensively highlights their potent antimicrobial and antibiofilm properties, particularly targeting multidrug-resistant bacterial strains where biofilms increase resistance up to 1000-fold. Furthermore, the review explores the potent cytotoxic and anticancer profiles of sponge-associated fungal metabolites, emphasizing mechanisms such as Chk2 kinase inhibition and the suppression of tumor cell migration. Additionally, the emerging field of marine dermocosmetics has been analyzed, detailing the role of fungal antioxidants, UV-photoprotective agents, and enzymatic inhibitors (targeting collagenase, elastase, and hyaluronidase) in anti-aging formulations. Through a PRISMA-based systematic evaluation, the biotechnological potential of these novel marine metabolites will be analyzed critically, providing a structured baseline for future drug discovery initiatives and clinical scale-up.
Keywords: Cytotoxicity; Dermocosmetics; Keywords: Antibiofilm; Marine fungi; secondary metabolites